Overview: Economic crises and human development - Conceição, Pedro; Kim, Namsuk; Zhang, Yanchun (Estudios Económicos de El Colegio de México, 2010)
In order to better understand the potential impact of the current global economic crisis on human development, we explore how human development indicators have been affected in past economic shocks. The literature on the human development impacts of short-term economic fluctuations suggest some stylized facts. First, there exists an asymmetry between rich and poor countries in terms of the magnitude of impacts of economic crises: Health and education outcomes in rich countries often improve during economic crises, while they deteriorate in poor countries. Second, economic expansions have less significant effects than economic contractions: the recovery in human development indicators is not as rapid and steep (if it occurs at all) as the deterioration that occurred during the economic downturn.